ASSESSING VULNERABILITY OF RURAL FARMING HOUSEHOLDS TO ENVIRONMENTAL PROBLEMS IN OGUN STATE SOUTH WEST NIGERIA - Oladeji, S. O.; Tolorunju, E. T.; Obayelu, A. E.; Omoare, A. M. (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the vulnerability level of the rural farming households to environmental problems in two selected agricultural zones of Ogun State Nigeria. A cross sectional sample of 160 farming households was drawn using multistage sampling techniques. Data were analyzed using descriptive statistics and principal component analysis. The study revealed that majority of the households’ head were males with mean of 48 years, (88.8%) With households sizes of between 5and 9 persons. Household vulnerability indices for environmental problems were negative for the two zones studied The study concluded that most of the farming households were vulnerable to environmental problems and crop yield decreased drastically over the years with unfavorable environmental conditions. The study therefore recommends that Farmers, should diversify farm land by planting crops in different locations as the environmental degradation induced hazards do not equally harm everywhere in a region.